Speaking and Reading Skills Challenges Kurdish EFL Students Expose from Teachers’ and Students’ Perspectives - Nooraldeen Kaka Amin, Hiwa; Zorab Azeez, Paiman (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
This study focuses on identifying the major challenges that high school EFL students experience in speaking and reading skills in target language. Although EFL students study English language for twelve years in the context of Iraqi Kurdistan, they still have challenges in language skills. Little research has been conducted to investigate the challenges of speaking and reading skills. A mixed approach was used for collecting data. With reference to selected high schools in Koya district, this study aims at identifying the major challenges that EFL high school students encounter in speaking and reading skills. The data was gathered from 15 high school teachers and 323students to understand students’ challenges of speaking and reading skills. Thematic analysis was used for interpreting the collected data from structured interviews of teachers and statistical analysis was used for interpreting the collected data from the students’ questionnaire. This study gives detailed explanations of speaking and reading skills challenges. It provides informed recommendations for identifying challenges and overcoming obstacles. Ultimately, the study provides practical and useful information, and recommendations for teachers and high school EFL students to address barriers. The results of the study revealed considerable and potential challenges to Kurdish EFL students in speaking and reading skills such as, linguistic and nonlinguistic challenges. It is suggested that students should be given appropriate learning environment, and linguistic competency to overcome obstacles.